A study on the awareness of halal food products among consumers in Kg. Bunga Tuaran / Mohd Sharizan Norfini - Norfini, Mohd Sharizan (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2009)
This study focus on the awareness of Halal food product among consumers in Kg, Bunga Tuaran. It was done with the purposes, to study the level of awareness on Halal food products among consumers, to examine differences of awareness on Halal food products among Muslim and Non-Muslim consumers also to examine differences of awareness on Halal food products among gender. For this study, the sample size is just around 80 respondents which are located in Kg. Bunga Tuaran. From the results, it shows that most of the respondents have a high level of awareness regarding this issue. Mostly, there are no significant differences on the awareness of halal food products either between religions also genders. Here, both religions and genders have a same perception regarding halal issue products, which is create through their awareness. At this point, halal is no longer just a purely religious issue, it is becoming a global symbol for quality assurance and lifestyle choice. So that, there is a need for recommendations to improve and enhance consumers awareness including identify target audience, create early exposure, handle effective programs, provide more research on similar study and involve many mass media in disseminate information to the public. The Halal industry needs its own voice and its own publication to stand by itself. This issue will be able to provide useful and updated information on the current requirement and practices for Halal food product.